La presión por rendir: estrés académico y burnout en bailarines-atletas universitarios durante entrenamientos intensivos - Longakit, Jet C.; Sayson, Minerva C.; Ompoc, Harlyn Mae S.; Almerol, Norman Julian; Toring-Aque, Lyndie; Aque , Felix Jr. M.; Bucad, Rovie Gretchel P.; Rodriguez, Deljun; Fajardo, Romeo (Sportis. Scientific Journal of School Sport, Physical Education and Psychomotricity, 2026)
This study examined the effect of academic stress on burnout among university dance athletes undergoing intensive training. While research has explored stress and performance in athletes, limited attention has been given to student dancers balancing academic and artistic demands. Guided by the Cognitive-Transactional Theory of Stress and Coping, the study analyzed how dimensions of academic stress predict burnout symptoms, including emotional exhaustion, detachment, and reduced accomplishment. A total of 243 Filipino student dancers aged 18–25 were purposively selected based on the following inclusion criteria: competitive experience at the national or international level, at least five years of formal dance training, and current academic enrollment. Using a descriptive-correlational design, participants completed the Educational Stress Scale for Adolescents (ESSA) and the School Burnout Inventory (SBI), and data were analyzed through multiple regression using IBM SPSS v28. Results showed that academic stress significantly predicted dance burnout, with study pressure emerging as the strongest predictor, followed by despondency, worry about grades, workload, and self-expectation. These findings underscore the need for institutional programs, such as stress-management training, academic accommodations, and mental-health support, to help student performers sustain both academic success and artistic performance.